The conceptualisation, implementation and management of research-led teaching in a developing country university - Batisani, Changu Chandapiwa (My University, 2020)
This thesis demonstrates that while there is a university rhetoric concerning how research and teaching are linked, the ideals and practices of these linkages are not obvious in both research–led and teaching–led universities. A division of labour among teaching staff and research staff persist in the two types of universities to the extent that this link becomes questionable. In an investigation of how research–led teaching (RLT) is conceptualised, implemented and managed in a teaching university in Botswana, this thesis identifies misalignment between institutional systems, structures and resources with RLT initiatives. Perceived institutional incentives, cultures of individual academic staff/ lecturers do not encourage the implementation of RLT. This tension therefore calls for higher education (HE) managers to deploy pragmatic strategies to actualise the link between research and teaching through aligning systems, resources, structures with university research - led teaching link strategies. The study adopted multiple theories to focus and organise an investigation of RLT in the context of a teaching university transiting to being a research–led university. The 7S McKinsey management model, aided in understating the general implementation and management of a strategy while Taylor’s model for managing the research and teaching nexus was critical in understanding the implementation of RLT in a university environment. The methodological approaches involved data collection within a concurrent mixed methods. The data were collected from institutional documents, focused group discussions with three groups of students, interviews with lecturers and a student survey. The study employed thematic analysis and descriptive statistics to analyse the data. This thesis has uncovered key findings under four broad areas, namely, “conceptualisation”, “value”, “approaches in RLT” and its “management”. In terms of how RLT is valued by lecturers and students, it is evident in this study that research-led teaching is valued because it has the potential to satisfy the needs of the labour market by enhancing graduate employability. This belief has also impacted on how the teaching approach is conceptualised. Beyond the confirmation of previous findings, the study proposes another dimension of conceptualising RLT that is influenced by the consumerist approach to Higher Education. It defines RLT as teaching that is based on the needs of the market. The approaches to actualising RLT were, therefore, those that involve students in research, field work assignment and researching the labour market and student needs. The study further reveals that RLT is not fully implemented because the university under study has adopted a passive approach to management, where the implementation is left to individual lecturers and the faculty. The study concludes with a contribution to theory by suggesting an implementation and management model that emphasises the need for systems, resources and structures that support RLT in a university setup. In terms of practice, it makes a contribution by coming up with other ways in which RLT can be understood, actualised and managed.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Education Leadership and Policy in the School of Education to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020